Basal implants and their importance in clinical Dentistry: Literature review (Research, Society and Development, 2024)
Background: Basal implants, also known as cortical implants, have a history dating back to the mid-20th century. Although they are not as well known or widely used as conventional dental implants, they have been gaining relevance in dentistry in recent years due to their effectiveness in specific clinical situations. Objective: evaluate clinical effectiveness, analyze their indications, contraindications, examine complications and success rate. Methods: the research was structured based on a search tree (PubMed, Google Scholar, ProQuest, Scopus), with keywords such as: Basal Implant. The languages: English, Portuguese and Spanish were used as limiters; open access articles, systematic reviews, meta-analysis, randomized clinical trials, case reports. We established a secondary selection based on the title and summary of the articles according to the objective of the study.Results: The initial search showed 3,099 studies whose title was related to the search patterns, of which 3,029 articles were excluded based on their title and abstract, thus resulting in 70 potentially relevant articles. After reading, 21 articles that did not meet the inclusion criteria were excluded: repeated. In this way, 49 articles were finally selected to carry out this review. Conclusions: Dental implants offer significant benefits in oral functionality, facial aesthetics, self-esteem and long-term health. However, there are important considerations that encompass postoperative care, costs, insurance coverage, and access to these treatments.